Syntactic design of children’s advertising texts: in the context of age, product, and media format - Xudayberganova, Maxbuba (The Lingua Spectrum, 2025)
This article analyzes the syntactic structure of advertising texts for children’s audiences in French and Uzbek languages using a linguistic approach. The main objective is identifying functional directions in sentence pattern selection, their informational load and impact strategies, including similarities and differences. The analysis employed structural-syntactic, psycholinguistic, semiotic, discursive, and comparative analysis methods. These methods enabled quantitative and qualitative determination of sentence composition, syntactic conciseness, imperative forms, rhetorical questions, asyndetic constructions, and repetitive word usage levels. The research proved that children’s age, advertised product type, and advertising media significantly influence sentence structure selection. The article’s scientific novelty lies in being among the first works conducting comprehensive comparative analysis of French and Uzbek children’s advertising text sentence structures through linguistic parameters related to age factor, product category, and media format. The obtained results contribute to deep understanding of syntactic features of children’s advertising language and comprehension of implementation mechanisms in unrelated languages.